Perbandingan Efektivitas T-spring Berdimensi Kawat 0,5 mm dan 0,6 mm terhadap Koreksi Gigi Malposisi Individual (Kajian pada Typodont) - Desyani, Ni Lluh S.; Anindita, Pritartha S.; Leman, Michael A. (e-GiGi, 2021)
Abstract: Malocclusion can trigger various health problems in the oral cavity. The simplest form of malocclusion is individual dental malposition which can be corrected by removable orthodontic appliances with active components T-springs made of 0.5 mm or 0.6 mm wire dimensions. This study was aimed to compare the effectiveness of the T-spring with wire dimensions of 0.5 mm and of 0.6 mm on the correction of individual dental malpositions. This was a pre-experimental study using a one-shot case study design. Study samples were divided into two groups, T-spring with wire dimensions of 0.5 mm and of 0.6 mm on removable orthodontic appliances attached to typodonts. The samples were activated, and the typodonts were immersed in warm water until the individual tooth malpositions were corrected. The number of activations and the average tooth movement each time the activation were calculated and analyzed. The numbers of T-spring activations with 0.5 mm and 0.6 mm wire dimensions were analyzed with the Mann-Whitney test that showed a p-value of 0.042 (p<0.05). The data of the mean tooth movement each time the T-spring was activated were analyzed with the independent sample t-test that obtained a p value of 0.016 (p<0.05). In conclusion, the T-spring with wire dimension of 0.5 mm is more effective in correcting individual dental malpositions than the T-Spring with wire dimensions of 0.6 mm.Keywords: tooth malposition; removable orthodontics; effectiveness of T-springÂ Abstrak: Maloklusi dapat memicu berbagai masalah kesehatan pada rongga mulut. Bentuk sederhana dari maloklusi yaitu malposisi gigi individual yang dapat dikoreksi dengan alat ortodonti lepasan dengan komponen aktif pegas T (T-spring) yang terbuat dari kawat berdimensi 0,5 mm atau 0,6 mm. Penelitian ini bertujuan untuk mengetahui perbandingan efektivitas T-spring dengan dimensi kawat 0,5 mm dan 0,6 mm terhadap koreksi malposisi gigi individual. Jenis penelitian yaitu pre-experimental dengan menggunakan one-shot case study design. Sampel penelitian dibagi menjadi dua kelompok yaitu T-spring dengan dimensi kawat 0,5 mm dan 0,6 mm pada alat ortodonti lepasan yang dipasang ke typodont. Sampel diaktivasi dan typodont direndam dalam air hangat hingga malposisi gigi individual terkoreksi. Jumlah aktivasi serta rerata jarak perpindahan gigi setiap kali T-spring diaktivasi dihitung dan dianalisis. Data jumlah aktivasi T-spring dimensi kawat 0,5 mm dan 0,6 mm dianalisis menggunakan uji Mann Whitney yang menunjukkan nilai p=0,042 (p<0,05). Data rerata jarak perpindahan gigi setiap kali T-spring diaktivasi dianalisis menggunakan uji independent sample t-test dan memperoleh nilai p=0,016 (p<0,05). Simpulan penelitian ini ialah T-spring dengan dimensi kawat 0,5 mm lebih efektif dalam mengoreksi malposisi gigi individual dibandingkan T-spring dengan dimensi kawat 0,6 mm.Kata kunci: malposisi gigi; ortodonti lepasan; efektivitas T-spring